Assessment of effective coral rehabilitated in Marine Protected Areas of south Vietnam - Ben, Hoang Xuan; Tuan, Vo Si; Hoang, Phan Kim (Vietnam Journal of Marine Science and Technology, 2021)
More than 20,300 fragment corals belonging to 24 species, eight genera and six families were rehabilitated in marine protected areas of south Vietnam. Mean survival rates of coral fragments ranged from 60–97.7%, the average growth rate of the branched corals was 4.8 mm/month meanwhile the foliose coral was 1.9 mm/month. The survival and growth rate of corals are different among areas because each coral species has different biological characteristics, structure colonies and due to differences in natural conditions each area. The results showed that the growth rate of corals will return to normal after 4 months rehabilitation. The factors affected the effective coral rehabilitation including: Coral reef predators, spatial competition among species, environmental conditions change due to human’s activities; and other factors such as hydrodynamic regimes, cutting fragment corals cause its injury damage. The rehabilitation and protection activities of coral reefs in marine protected areas should be continued and expanded, contributing to the protection of biodivesity, marine resource and sustainable coral reefs ecosystem development.